Self-diverting acidifying agent based on nano process and preparation method of self-diverting acidifying agent
The self-steering acidifier prepared through nanoprocessing uses quartz sand and polyamino acid technology to solve the problems of high cost of acidification and unsatisfactory temperature resistance in the oil field, and realize the effective acidification of high-temperature deep wells, improving the acidification effect and resistance of acidification in the oil field. Warmness.
Patent Information
- Application Number
- CN202411409830.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-13
AI Technical Summary
The existing acidification shift technology has problems such as high cost, complex operation, easy formation of sulfide precipitation, and poor temperature resistance in oil fields, making it difficult to effectively solve the acidification needs of high-temperature deep wells.
Using a self-steering acidifier based on nanoprocess, quartz sand is sonicated, β-cyclodextrin and silane coupling agent is introduced, and free radical polymerization is carried out by combining polyamino acids and initiators. Modified quartz sand is added to form temperature resistance and resistance. Shearing acidifier to avoid secondary damage to the formation.
The self-steering ability of the acid solution is achieved, the acidification effect is improved, the formation damage is reduced, the temperature resistance and shear resistance of the acidifier are enhanced, and the acidification effect is significantly improved.
Smart Images

Figure CN119119998A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oilfield acidification, and in particular relates to a self-steering acidifier based on nanotechnology and a preparation method thereof. Background Art
[0002] When the development of an oil field enters the middle and late stages, the formation pressure decreases, the reservoir driving capacity weakens, and the oil field production capacity is greatly reduced. In order to ensure the stable and high production of the oil field, the oil field can be developed by water injection. This method can effectively maintain the formation energy and maintain the production capacity of the oil field. Therefore, water drive has become one of the main and very effective means of stabilizing the pressure and increasing the production of the oil field. However, due to the problems of the solid content, oil content, and various metal ion content of the injected fluid itself, as well as the compatibility of the injected fluid with the formation, the blockage of the near-wellbore area and deep area of the water injection well is becoming more and more serious, affecting the water injection effect, and then affecting the production capacity of the oil field. Acidizing operations can dissolve pollutants such as scale that blocks the near-wellbore area, clay particles that migrate in the formation, and can effectively improve the permeability of the near-wellbore area. It is the main means to remove the blockage of the near-wellbore area of the water injection well, realize the injection of water injection wells, and increase the production of oil and gas wells. When acid is injected into the formation, it will follow the principle of least resistance and enter the formation with higher permeability first, while bypassing the formation with lower permeability. This will lead to problems such as uneven distribution of acid in the formation and unsatisfactory acidizing effect. Acidizing diversion technology is an important method to solve this problem.
[0003] Existing acidizing diversion technologies can be divided into mechanical diversion and chemical diversion. Mechanical diversion technology is limited in application due to its high cost and complex operation. Chemical diversion can be divided into particle diversion, cross-linked polymer diversion, foam diversion and viscoelastic surfactant diversion. Although this type of diversion technology has a good diversion effect, it still has certain problems: in particle diversion technology, the cost of oil-soluble particle diversion agent is too high, the cross-linked system formed by cross-linked polymer diversion technology is not easy to break, and the metal cross-linking agent is easy to form sulfide precipitation in sulfur-containing wells, which is easy to cause secondary damage to the formation; foam diversion technology is greatly affected by temperature and formation permeability, and its application is limited; viscoelastic surfactant diversion technology has problems such as large addition, high cost, and unsatisfactory temperature resistance. Therefore, it is urgent to develop a new acidizing agent and matching diversion technology to solve the above problems. Summary of the invention
[0004] The primary purpose of the present invention is to provide a self-diverting acidifier based on nanotechnology and a preparation method thereof. The acidifier obtained according to the present invention has obvious self-diverting acidizing effect and can meet the acidification and acid fracturing requirements of high-temperature deep wells.
[0005] To this end, the present invention provides the following technical solutions.
[0006] One aspect of the present invention provides a method for preparing a self-diverting acidifier based on nanotechnology, the method comprising the following steps:
[0007] Quartz sand with an average particle size of 80 to 120 meshes is placed in a hydrofluoric acid solution with a volume concentration of 1 to 5%, and ultrasonically treated at a power of 600 to 1000 W for 20 to 60 seconds, then taken out, washed, and dried to obtain surface-etched quartz sand;
[0008] Dissolve β-cyclodextrin in 1-5 mol / L acidic solution according to a mass volume ratio of 1 g: 50-100 mL, then add the obtained surface-etched quartz sand and silane coupling agent, stir at 40-60° C. for 30-60 min, stand for 8-12 h after the stirring, centrifuge after the standing, wash, dry, grind and pass through an 800-1000 mesh sieve to obtain modified quartz sand powder;
[0009] The polyamino acid is dissolved in water to obtain a polyamino acid solution with a concentration of 1 to 5 wt%, and then mixed monomers are added to the obtained polyamino acid solution in sequence, and an initiator is added to react to obtain a polymerization product, and then modified quartz powder is added to the obtained polymerization product and stirred evenly, and finally the obtained solid product is washed, dried, and crushed to obtain a self-steering acidifier.
[0010] In a preferred embodiment of the present invention, the acidic solution is selected from one or a mixture of two or more of the following acids, and the acids include: hydrochloric acid, nitric acid, citric acid, malic acid, acetic acid, and oxalic acid.
[0011] In a preferred embodiment of the present invention, the added amount of the surface etching quartz sand is 0.05 to 0.2 times the mass of β-cyclodextrin.
[0012] In a preferred embodiment of the present invention, the silane coupling agent is selected from any one of bis(triethoxysilyl)methane, bis(triethoxysilyl)ethane, (triethoxysilyl)methanol and (triethoxysilyl)methane.
[0013] In a preferred embodiment of the present invention, the added amount of the silane coupling agent is 0.1-0.3% of the mass of β-cyclodextrin.
[0014] In a preferred embodiment of the present invention, the polyamino acid is selected from 3 -2×10 4 A mixture of one or more of polyleucine, polyglutamic acid, polyaspartic acid and polylysine.
[0015] In a preferred embodiment of the present invention, the mixed monomer is prepared by mixing acrylamide, N-vinyl pyrrolidone, the first monomer and the second monomer in equal weight ratios, and the added amount of the mixed monomer is 0.5 to 2 times the weight of the polyamino acid.
[0016] In a preferred embodiment of the present invention, the first monomer is selected from one or a mixture of two or more of N-methyldiethanolamine, N,N,N',N'-tetramethyl-p-phenylenediamine, and N,N-dimethylbenzylamine.
[0017] In a preferred embodiment of the present invention, the second monomer is selected from one or a mixture of two or more of cocoamidopropyl betaine, alkyl dimethyl betaine, and alkylamido betaine.
[0018] In a preferred embodiment of the present invention, the initiator is selected from any one of sodium persulfate, potassium persulfate and ammonium persulfate.
[0019] In a preferred embodiment of the present invention, the amount of the initiator added is 0.2-0.8% of the mass of the mixed monomers.
[0020] In a preferred embodiment of the present invention, the added amount of the modified quartz powder is 0.1-0.3% of the mass of the polymerization product.
[0021] By means of the above technical solution, the present invention has at least the following advantages:
[0022] 1. The self-diverting acidifier of the present invention uses polyamino acid as a matrix, introduces four monomers with different properties and performs free radical polymerization under the action of an initiator, so that the viscosity of the obtained monomer-grafted polyamino acid polymer is increased, so that the acid solution is gradually diverted to the medium and low permeability layers, achieving the purpose of self-diversion, which avoids the secondary damage to the formation caused by traditional acid diverting agents.
[0023] 2. A small amount of modified quartz sand is also added to the self-steering acidifier of the present invention. The modified quartz sand of the present invention is surface-etched quartz sand obtained by etching the surface of quartz sand with hydrofluoric acid. Then, the surface-etched quartz sand and the acid-decomposed β-cyclodextrin are connected together under the bridging effect of the silane coupling agent to obtain the modified quartz sand. By adding a small amount of modified quartz sand, the temperature resistance and shear resistance of the obtained self-steering acidifier can be increased, and the degumming property of the acidifier can be improved, so that it is easy to flow back and has little damage to the reservoir.
[0024] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the steering performance of the acidified fluid with a mass content of 1%;
[0026] Figure 2 is the steering performance of the acidizing fluid with a mass content of 1.5%;
[0027] Figure 3 The effect of sodium chloride concentration on the diversion performance of the acidizing fluid;
[0028] Figure 4 The effect of shear rate on the diversion performance of the acidizing fluid;
[0029] Figure 5 The effect of temperature on the steering performance of the acidizing fluid. DETAILED DESCRIPTION
[0030] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Unless otherwise specified, the percentage content involved in the present invention refers to mass percentage for solid-liquid mixing and solid-solid mixing, and refers to volume percentage for liquid-liquid mixing.
[0032] Unless otherwise specified, the percentage concentrations referred to in the present invention all refer to final concentrations, which refer to the percentage of the added component in the system after the addition of the component.
[0033] The temperature parameters in the present invention, if not specifically limited, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument.
[0034] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0035] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0036] Embodiment 1:
[0037] Quartz sand with an average particle size of 100 meshes was placed in a hydrofluoric acid solution with a volume concentration of 3%, and ultrasonically treated at a power of 800 W for 40 seconds. The sand was then taken out, washed, and dried to obtain surface-etched quartz sand.
[0038] β-cyclodextrin was dissolved in 3 mol / L citric acid solution at a mass-to-volume ratio of 1 g:75 mL, and then the surface-etched quartz sand obtained (the added amount was 0.1 times the mass of β-cyclodextrin) and bis(triethoxysilyl)methane (the added amount was 0.2% of the mass of β-cyclodextrin) were added, stirred at 50°C for 45 min, allowed to stand for 10 h after the stirring, and centrifuged after the standing period. The obtained precipitate was washed, dried, ground and passed through a 1000-mesh sieve to obtain modified quartz sand powder.
[0039] The molecular weight is 5×10 3 Da of polyleucine is dissolved in water to obtain a polyleucine solution with a concentration of 3wt%, and then mixed monomers (acrylamide, N-vinyl pyrrolidone, N-methyldiethanolamine and cocamidopropyl betaine are mixed in equal mass ratios, and the added amount of the mixed monomers is 0.1 times the mass of the polyleucine) are added to the obtained polyleucine solution in sequence, and ammonium persulfate (the added amount is 0.5% of the mass of the mixed monomers) is added to react to obtain a polymerization product, and then modified quartz powder (the added amount is 0.2% of the mass of the polymerization product) is added to the obtained polymerization product and stirred evenly, and finally the obtained solid product is washed, dried and crushed to obtain a self-steering acidifier.
[0040] Embodiment 2:
[0041] Quartz sand with an average particle size of 80 meshes was placed in a hydrofluoric acid solution with a volume concentration of 1%, and ultrasonically treated at a power of 1000 W for 20 seconds. The sand was then taken out, washed, and dried to obtain surface-etched quartz sand.
[0042] β-cyclodextrin was dissolved in 1 mol / L acetic acid solution at a mass-to-volume ratio of 1 g:100 mL, and then the obtained surface-etched quartz sand (the added amount was 0.2 times the mass of β-cyclodextrin) and bis(triethoxysilyl)ethane (the added amount was 0.3% of the mass of β-cyclodextrin) were added, stirred at 40°C for 60 min, allowed to stand for 8 h after the stirring, and centrifuged after the standing period. The obtained precipitate was washed, dried, ground and passed through a 1000-mesh sieve to obtain modified quartz sand powder.
[0043] The molecular weight is 5×10 3Da of polyglutamic acid is dissolved in water to obtain a polyglutamic acid solution with a concentration of 5wt%, and then mixed monomers (acrylamide, N-vinyl pyrrolidone, N,N,N',N'-tetramethyl-p-phenylenediamine and alkyl dimethyl betaine are mixed in equal mass ratios, and the added amount of the mixed monomers is 0.5 times the mass of the polyglutamic acid) are added to the obtained polyglutamic acid solution in sequence, and ammonium persulfate (the added amount is 0.2% of the mass of the mixed monomers) is added to react to obtain a polymerization product, and then modified quartz powder (the added amount is 0.1% of the mass of the polymerization product) is added to the obtained polymerization product and stirred evenly, and finally the obtained solid product is washed, dried and crushed to obtain a self-steering acidifier.
[0044] Embodiment 3:
[0045] Quartz sand with an average particle size of 120 meshes was placed in a hydrofluoric acid solution with a volume concentration of 5%, and ultrasonically treated at a power of 600 W for 60 seconds. The sand was then taken out, washed, and dried to obtain surface-etched quartz sand.
[0046] β-cyclodextrin was dissolved in 5 mol / L oxalic acid solution at a mass-to-volume ratio of 1 g:50 mL, and then the obtained surface-etched quartz sand (the added amount was 0.05 times the mass of β-cyclodextrin) and (triethoxysilyl)methane (the added amount was 0.1% of the mass of β-cyclodextrin) were added, stirred at 60°C for 30 min, allowed to stand for 12 h after the stirring, and centrifuged after the standing period. The obtained precipitate was washed, dried, ground and passed through a 1000-mesh sieve to obtain modified quartz sand powder.
[0047] The molecular weight is 5×10 3 Polyaspartic acid of Da is dissolved in water to obtain a polyaspartic acid solution with a concentration of 1wt%, and then mixed monomers (acrylamide, N-vinyl pyrrolidone, N,N-dimethylbenzylamine and alkylamide betaine are mixed in equal mass ratios, and the added amount of the mixed monomers is twice the mass of the polyaspartic acid) are added to the obtained polyaspartic acid solution in sequence, and ammonium persulfate (the added amount is 0.8% of the mass of the mixed monomers) is added to react to obtain a polymerization product, and then modified quartz powder (the added amount is 0.3% of the mass of the polymerization product) is added to the obtained polymerization product and stirred evenly, and finally the obtained solid product is washed, dried and crushed to obtain a self-steering acidifier.
[0048] Comparative Example 1:
[0049] The only difference between this comparative example and Example 1 is that the quartz sand is not etched, and the rest is consistent with Example 1, specifically:
[0050] β-cyclodextrin was dissolved in 3 mol / L citric acid solution at a mass-to-volume ratio of 1 g:75 mL, and then 100 mesh quartz sand (the amount added was 0.1 times the mass of β-cyclodextrin) and bis(triethoxysilyl)methane (the amount added was 0.2% of the mass of β-cyclodextrin) were added, stirred at 50°C for 45 min, allowed to stand for 10 h after the stirring, and centrifuged after the standing period. The resulting precipitate was washed, dried, ground and sieved through a 1000 mesh sieve to obtain modified quartz sand powder.
[0051] The molecular weight is 5×10 3 Da of polyleucine is dissolved in water to obtain a polyleucine solution with a concentration of 3wt%, and then mixed monomers (acrylamide, N-vinyl pyrrolidone, N-methyldiethanolamine and cocamidopropyl betaine are mixed in equal mass ratios, and the added amount of the mixed monomers is 0.1 times the mass of the polyleucine) are added to the obtained polyleucine solution in sequence, and ammonium persulfate (the added amount is 0.5% of the mass of the mixed monomers) is added to react to obtain a polymerization product, and then modified quartz powder (the added amount is 0.2% of the mass of the polymerization product) is added to the obtained polymerization product and stirred evenly, and finally the obtained solid product is washed, dried and crushed to obtain a self-steering acidifier.
[0052] Comparative Example 2:
[0053] The only difference between this comparative example and Example 1 is that the quartz sand is not modified with a silane coupling agent, and the rest is consistent with Example 1, specifically:
[0054] Quartz sand with an average particle size of 100 meshes was placed in a hydrofluoric acid solution with a volume concentration of 3%, and ultrasonically treated at a power of 800 W for 40 seconds. It was then taken out, washed, dried, ground, and passed through a 1000 mesh sieve to obtain surface-etched quartz sand powder.
[0055] The molecular weight is 5×10 3 Da of polyleucine is dissolved in water to obtain a polyleucine solution with a concentration of 3wt%, and then mixed monomers (acrylamide, N-vinyl pyrrolidone, N-methyldiethanolamine and cocamidopropyl betaine are mixed in equal mass ratios, and the added amount of the mixed monomers is 0.1 times the mass of the polyleucine) are added to the obtained polyleucine solution in sequence, and ammonium persulfate (the added amount is 0.5% of the mass of the mixed monomers) is added to react to obtain a polymerization product, and then surface etching quartz sand powder (the added amount is 0.2% of the mass of the polymerization product) is added to the obtained polymerization product and stirred evenly, and finally the obtained solid product is washed, dried and crushed to obtain a self-steering acidifier.
[0056] Comparative Example 3:
[0057] The only difference between this comparative example and Example 1 is that the quartz sand is not etched and the silane coupling agent is not modified, and the rest is consistent with Example 1, specifically:
[0058] The molecular weight is 5×10 3 Da of polyleucine is dissolved in water to obtain a polyleucine solution with a concentration of 3wt%, and then mixed monomers (acrylamide, N-vinyl pyrrolidone, N-methyldiethanolamine and cocamidopropyl betaine are mixed in equal mass ratios, and the added amount of the mixed monomers is 0.1 times the mass of the polyleucine) are added to the obtained polyleucine solution in sequence, and ammonium persulfate (the added amount is 0.5% of the mass of the mixed monomers) is added to react to obtain a polymerization reaction product, and the obtained solid product is washed, dried, and crushed to obtain a self-steering acidifier.
[0059] Comparative Example 4:
[0060] The only difference between this comparative example and Example 1 is that the first monomer N-methyldiethanolamine is not added, and the rest is consistent with Example 1, specifically:
[0061] Quartz sand with an average particle size of 100 meshes was placed in a hydrofluoric acid solution with a volume concentration of 3%, and ultrasonically treated at a power of 800 W for 40 seconds. The sand was then taken out, washed, and dried to obtain surface-etched quartz sand.
[0062] β-cyclodextrin was dissolved in 3 mol / L citric acid solution at a mass-to-volume ratio of 1 g:75 mL, and then the surface-etched quartz sand obtained (the added amount was 0.1 times the mass of β-cyclodextrin) and bis(triethoxysilyl)methane (the added amount was 0.2% of the mass of β-cyclodextrin) were added, stirred at 50°C for 45 min, allowed to stand for 10 h after the stirring, and centrifuged after the standing period. The obtained precipitate was washed, dried, ground and passed through a 1000-mesh sieve to obtain modified quartz sand powder.
[0063] The molecular weight is 5×10 3 Da of polyleucine is dissolved in water to obtain a polyleucine solution with a concentration of 3wt%, and then mixed monomers (acrylamide, N-vinyl pyrrolidone and cocamidopropyl betaine are mixed in equal mass ratios, and the added amount of the mixed monomers is 0.1 times the mass of the polyleucine) are added to the obtained polyleucine solution in sequence, and ammonium persulfate (the added amount is 0.5% of the mass of the mixed monomers) is added to react to obtain a polymerization product, and then modified quartz powder (the added amount is 0.2% of the mass of the polymerization product) is added to the obtained polymerization product and stirred evenly, and finally the obtained solid product is washed, dried and crushed to obtain a self-steering acidifier.
[0064] Comparative Example 5:
[0065] The only difference between this comparative example and Example 1 is that the second monomer cocamidopropyl betaine is not added, and the rest is consistent with Example 1, specifically:
[0066] Quartz sand with an average particle size of 100 meshes was placed in a hydrofluoric acid solution with a volume concentration of 3%, and ultrasonically treated at a power of 800 W for 40 seconds. The sand was then taken out, washed, and dried to obtain surface-etched quartz sand.
[0067] β-cyclodextrin was dissolved in 3 mol / L citric acid solution at a mass-to-volume ratio of 1 g:75 mL, and then the surface-etched quartz sand obtained (the added amount was 0.1 times the mass of β-cyclodextrin) and bis(triethoxysilyl)methane (the added amount was 0.2% of the mass of β-cyclodextrin) were added, stirred at 50°C for 45 min, allowed to stand for 10 h after the stirring, and centrifuged after the standing period. The obtained precipitate was washed, dried, ground and passed through a 1000-mesh sieve to obtain modified quartz sand powder.
[0068] The molecular weight is 5×10 3 Da of polyleucine is dissolved in water to obtain a polyleucine solution with a concentration of 3wt%, and then mixed monomers (acrylamide, N-vinyl pyrrolidone and N-methyldiethanolamine are mixed in equal mass ratios, and the added amount of the mixed monomers is 0.1 times the mass of the polyleucine) are added to the obtained polyleucine solution in sequence, and ammonium persulfate (the added amount is 0.5% of the mass of the mixed monomers) is added to react to obtain a polymerization product, and then modified quartz powder (the added amount is 0.2% of the mass of the polymerization product) is added to the obtained polymerization product and stirred evenly, and finally the obtained solid product is washed, dried and crushed to obtain a self-steering acidifier.
[0069] Comparative Example 6:
[0070] The only difference between this comparative example and Example 1 is that the first monomer N-methyldiethanolamine and the second monomer cocoamidopropyl betaine are not added, and the rest is consistent with Example 1, specifically:
[0071] Quartz sand with an average particle size of 100 meshes was placed in a hydrofluoric acid solution with a volume concentration of 3%, and ultrasonically treated at a power of 800 W for 40 seconds. The sand was then taken out, washed, and dried to obtain surface-etched quartz sand.
[0072] β-cyclodextrin was dissolved in 3 mol / L citric acid solution at a mass-to-volume ratio of 1 g:75 mL, and then the surface-etched quartz sand obtained (the added amount was 0.1 times the mass of β-cyclodextrin) and bis(triethoxysilyl)methane (the added amount was 0.2% of the mass of β-cyclodextrin) were added, stirred at 50°C for 45 min, allowed to stand for 10 h after the stirring, and centrifuged after the standing period. The obtained precipitate was washed, dried, ground and passed through a 1000-mesh sieve to obtain modified quartz sand powder.
[0073] The molecular weight is 5×10 3 Da of polyleucine is dissolved in water to obtain a polyleucine solution with a concentration of 3wt%, and then mixed monomers (acrylamide and N-vinyl pyrrolidone are mixed in equal mass ratios, and the added amount of the mixed monomers is 0.1 times the mass of the polyleucine) are added to the obtained polyleucine solution in sequence, and ammonium persulfate (the added amount is 0.5% of the mass of the mixed monomers) is added to react to obtain a polymerization product, and then modified quartz powder (the added amount is 0.2% of the mass of the polymerization product) is added to the obtained polymerization product and stirred evenly, and finally the obtained solid product is washed, dried, and crushed to obtain a self-steering acidifier.
[0074] Test 1: Evaluation of the steering performance of a self-steering acidifier
[0075] The self-steering acidifiers obtained in Examples 1-3 and Comparative Examples 1-6 were added to a 20% HCl solution to obtain self-steering acid solutions with mass contents of 1.0% and 1.5%, respectively. Different masses of calcium carbonate powder were added to the obtained self-steering acid solutions, and after complete reaction at 30°C, steering acid solutions with different acid-rock reaction degrees were obtained. The steering acid solutions with different acid-rock reaction degrees were poured into the sample cup of a six-speed rotary viscometer, and the apparent viscosity of the steering acid solution was measured at 100 r / min. Three times the reading can be regarded as the steering acid solution at 170s. –1 The apparent viscosity under Figure 1-2 shown.
[0076] like Figure 1-2As shown in the figure, within a certain range, the apparent viscosity of the acid solution with different acidulant contents increases with the increase of calcium carbonate. This is because during the acid-rock reaction, the CaCl2 in the acid solution gradually increases, continuously enhancing the hydrophobic association of the hydrophobic chain of the acidulant, which is manifested as a continuous increase in the apparent viscosity on a macroscopic scale. The higher the content of the self-steering acidulant, the greater the apparent viscosity after the same mass of calcium carbonate reacts with it, indicating that the acidulant acid solution has good steering performance. In the acidizing solution with a content of 1.0%, the apparent viscosity can reach a maximum of 352.1 mPa·s, corresponding to the acidizing solution composed of the acidifier of Example 2, while the apparent viscosities of the acidizing solutions of Comparative Examples 1-6 are: 344 mPa·s, 342.3 mPa·s, 338.5 mPa·s, 309.1 mPa·s, 320.2 mPa·s, and 267.1 mPa·s, respectively; in the acidizing solution with a content of 1.5%, the apparent viscosity can reach a maximum of 612.1 mPa·s, corresponding to the acidizing solution composed of the acidifier of Example 3, while the apparent viscosities of the acidizing solutions of Comparative Examples 1-6 are: 581.5 mPa·s, 568.2 mPa·s, 542.7 mPa·s, 506.3 mPa·s, 521.5 mPa·s, and 468.3 mPa·s, respectively.
[0077] Compared with the acidified solution composed of the acidifier of Comparative Examples 1-6, the apparent viscosity of the acidified solution composed of the acidifier of Examples 1-3 is higher at 1.0% and 1.5% respectively. This result shows that the acidifier of Examples 1-3 has excellent steering performance compared with the acidifier of Comparative Examples 1-6.
[0078] In order to further study the diversion performance of the above acidified solutions in the formation with high water mineralization, different amounts of sodium chloride (based on the total mass of HCl, the same below) were added to the acidified solution with a content of 1.5% at 60°C, and the amount of calcium carbonate added was 40g. The effect of different amounts of sodium chloride on the diversion performance of the acidified solutions composed of Example 1 and Comparative Examples 1-6 was studied. The results are as follows: Figure 3 shown.
[0079] like Figure 3As shown, the apparent viscosity of the acid solution containing sodium chloride and the acid solution not containing sodium chloride increases with the progress of the acid-rock reaction, indicating that the addition of sodium chloride will not affect the thickening performance of each acid solution. Compared with the acidizing solutions composed of comparative examples 1-6, the acidizing solution of Example 1 is more sensitive to sodium chloride, which is specifically manifested in that the apparent viscosity increases with the increase of the sodium chloride content. This shows that the addition of sodium chloride has little effect on the steering performance of each acidifier, and the acid solution of Example 1 has good salt resistance. When the sodium chloride content is 5%, the apparent viscosity of the acidizing solution of Example 1 is 317.5 mPa·s, while the apparent viscosities of the acidizing solutions of Comparative Examples 1-6 are 283.7 mPa·s, 269.9 mPa·s, 258 mPa·s, 250.6 mPa·s, 258.7 mPa·s, and 196.3 mPa·s, respectively, which are significantly lower than the apparent viscosity of the acidizing solution of Example 1. This result shows that Example 1 has higher salt resistance.
[0080] In order to further investigate the effect of shearing and temperature on the residual acid viscosity, an acidified solution with a hydrochloric acid concentration of 20% and an acidulant concentration of 3% was prepared, in which 40 g of calcium carbonate was added. The residual acid viscosity at 90 °C and the shear rate at 170 s were measured. -1 The residual acid viscosity changes with temperature under shear rate. The results are shown in Figure 4-5 .
[0081] like Figure 4 As shown in the figure, at a temperature of 90 °C, with the increase of shear rate, the viscosity of each group of acid solutions showed a significant downward trend, with obvious shear thinning, but at a shear rate of 200s -1 When the viscosity of the acid solution in Example 1 is 223.4 mPa·s, the viscosity of the acid solution in Comparative Examples 1-6 is 202.3 mPa·s, 191.2 mPa·s, 180.8 mPa·s, 185.7 mPa·s, 188.2 mPa·s, and 153.4 mPa·s, respectively, which is significantly lower than that in Example 1. Figure 5 As shown, the shear rate is maintained at 170s -1 Under the condition of no change, the viscosity of the acid solution tends to decrease with the increase of temperature, but the viscosity of the acid solution of Example 1 can still reach 242 mPa·s at 90°C, while the viscosity of the acid solution of Comparative Examples 1-6 are 225.5 mPa·s, 216.4 mPa·s, 194.5 mPa·s, 202.1 mPa·s, 209.4 mPa·s and 178.5 mPa·s, respectively, which are significantly lower than the viscosity of the acid solution of Example 1.
[0082] The above results show that compared with comparative examples 1-6, the acidulant of example 1 of the present invention has better shear resistance and temperature resistance, and can ensure that the diversion ability of the acid solution during the acidizing process is not affected by reservoir shear and temperature.
[0083] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a self-diverting acidifier based on nanotechnology, characterized in that: The method comprises the following steps: Quartz sand with an average particle size of 80 to 120 meshes is placed in a hydrofluoric acid solution with a volume concentration of 1 to 5%, and ultrasonically treated at a power of 600 to 1000 W for 20 to 60 seconds, then taken out, washed, and dried to obtain surface-etched quartz sand; Dissolve β-cyclodextrin in a 1-5 mol / L acidic solution according to a mass volume ratio of 1 g: 50-100 mL, then add the obtained surface-etched quartz sand and the silane coupling agent, stir at 40-60° C. for 30-60 min, let stand for 8-12 h after the stirring, centrifuge after the standing, wash, dry, grind and pass through an 800-1000 mesh sieve to obtain modified quartz sand powder; The polyamino acid is dissolved in water to obtain a polyamino acid solution with a concentration of 1 to 5 wt%, and then mixed monomers are added to the obtained polyamino acid solution in sequence, and an initiator is added to react to obtain a polymerization product, and then modified quartz powder is added to the obtained polymerization product and stirred evenly, and finally the obtained solid product is washed, dried, and crushed to obtain a self-steering acidifier.
2. The preparation method according to claim 1, characterized in that: The acidic solution is selected from one or a mixture of two or more of the following acids, and the acids include: hydrochloric acid, nitric acid, citric acid, malic acid, acetic acid, and oxalic acid.
3. The preparation method according to claim 1, characterized in that: The added amount of the surface etching quartz sand is 0.05 to 0.2 times the mass of β-cyclodextrin.
4. The preparation method according to claim 1, characterized in that: The silane coupling agent is selected from any one of bis(triethoxysilyl)methane, bis(triethoxysilyl)ethane, (triethoxysilyl)methanol, and (triethoxysilyl)methane; The added amount of the silane coupling agent is 0.1-0.3% of the mass of the β-cyclodextrin.
5. The preparation method according to claim 1, characterized in that: The polyamino acid is selected from a molecular weight of 1×10 3 -2×10 4 One or a mixture of two or more of polyleucine, polyglutamic acid, polyaspartic acid and polylysine between Da.
6. The preparation method according to claim 1, characterized in that: The mixed monomer is prepared by mixing acrylamide, N-vinyl pyrrolidone, the first monomer and the second monomer in equal weight ratios, and the added amount of the mixed monomer is 0.5 to 2 times the weight of the polyamino acid.
7. The preparation method according to claim 6, characterized in that: The first monomer is selected from one or a mixture of two or more of N-methyldiethanolamine, N,N,N',N'-tetramethyl-p-phenylenediamine, and N,N-dimethylbenzylamine.
8. The preparation method according to claim 6, characterized in that: The second monomer is selected from one or a mixture of two or more of cocamidopropyl betaine, alkyl dimethyl betaine, and alkyl amide betaine.
9. The preparation method according to claim 1, characterized in that: The initiator is selected from any one of sodium persulfate, potassium persulfate, and ammonium persulfate; The added amount of the initiator is 0.2-0.8% of the mass of the mixed monomers.
10. The preparation method according to claim 1, characterized in that: The added amount of the modified quartz powder is 0.1-0.3% of the mass of the polymerization product.
